Optimalisasi Kinerja Pegawai Melalui peran Motivasi Kerja dari Aspek Disiplin Kerja, Kompetensi dan Komunikasi pada Polres Klaten - Lilis Sulistyani; Bintoro Iswahyudi (STIE AUB Surakarta, 2026)
This study aims to determine, test, and analyze the significance of the influence of work discipline, competence, and communication on work motivation and employee performance at the Klaten District Police (Polres Klaten). Data collection was conducted using questionnaires. A census technique was employed, utilizing the entire population of 50 respondents as the sample. Data analysis involved instrument testing, linearity testing, hypothesis testing, and path analysis. The t-test results demonstrate that work discipline and competence have a significant effect on work motivation, whereas communication does not; work discipline, communication, and work motivation significantly affect performance, while competence does not have a significant effect on employee performance. The F test results confirm that work discipline, competence, communication, and work motivation collectively have a significant effect on employee performance. The total coefficient of determination (R²) is 0.973, indicating that 97.3% of employee performance is explained by work discipline, competence, communication, and work motivation, while the remaining 2.7% is explained by factors outside the research model, such as compensation, leadership, and others. Path analysis reveals that the direct influence of communication on employee performance constitutes an effective pathway for enhancing performance. Work motivation effectively mediates the influence of competence on employee performance but fails to mediate the influence of work discipline and communication on employee performance.